EDUCATION DIPLOMACY: UNDERSTANDING GLOBAL DYNAMICS IN INTERACTIVE AND INCLUSIVE CURRICULUM DESIGN - Akib Akib (International Journal of Teaching and Learning, 2025)
The role of education diplomacy in shaping an interactive and inclusive curriculum in the era of globalisation. Facing the challenges of an increasingly connected world, education must be able to build multicultural skills and critical thinking. By utilising cultural exchange and international collaboration, curricula can be adapted to respond to both global and local needs. This approach not only improves the quality of education but also promotes social awareness and diversity in the learning environment. Thus, this study concludes that by understanding and integrating global dynamics in curriculum design, education can effectively prepare students to actively participate in a globalised society and address the complex challenges of the 21st century.